2022
DOI: 10.1101/2022.12.30.521993
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A multi-omicNicotiana benthamianaresource for fundamental research and biotechnology

Abstract: Nicotiana benthamiana is an invaluable model plant and biotechnology platform. To further improve its usefulness and versatility, we have produced high quality chromosome level genome assemblies and multi-omic datasets for both the ubiquitously used LAB strain and a distantly related wild accession, QLD, as well as mapping their single nucleotide polymorphisms with two additional laboratory and four additional wild accessions. LAB and QLD have many genetic, functional, and metabolic differences. These coupled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 49 publications
2
26
0
Order By: Relevance
“…The protein also showed enhanced accumulation following both P19 expression, and co‐expression of P19 and H5 (Table 1). To the best of our knowledge, this HSP90 has never been formally characterized in N. benthamiana , although it is annotated as a putative endoplasmin homologue in the improved genome assembly recently published for this plant species (Ranawaka et al ., 2023). Protein sequence alignments showed that this particular HSP90 homologue shares high homology to Arabidopsis SHEPHERD (AtSHD; AT4G24190), an ER‐resident chaperone involved in the folding of CLAVATA proteins that regulate meristem growth (Ishiguro et al ., 2002).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The protein also showed enhanced accumulation following both P19 expression, and co‐expression of P19 and H5 (Table 1). To the best of our knowledge, this HSP90 has never been formally characterized in N. benthamiana , although it is annotated as a putative endoplasmin homologue in the improved genome assembly recently published for this plant species (Ranawaka et al ., 2023). Protein sequence alignments showed that this particular HSP90 homologue shares high homology to Arabidopsis SHEPHERD (AtSHD; AT4G24190), an ER‐resident chaperone involved in the folding of CLAVATA proteins that regulate meristem growth (Ishiguro et al ., 2002).…”
Section: Resultsmentioning
confidence: 99%
“…Transient nature of the H5‐induced UPR suggests that enhanced ERQC and ERAD functions were sufficient to cope with ER stress imposed by expression of the HA protein, as opposed to the expression of an antibody that induced stronger and more sustained activation of the UPR. Overall, this work expands our understanding of host–plant responses to foreign protein expression, in addition of providing the research community with a useful set of marker genes to study ER stress and associated UPR in N. benthamiana , a model plant and host of choice for molecular farming and study of plant immunity (Bally et al ., 2018; Chung et al ., 2022; Goodin et al ., 2008; Ranawaka et al ., 2023). Conserved molecular mechanisms linked to the activation of UPR in N. benthamiana are further discussed.…”
Section: Introductionmentioning
confidence: 99%
“…N. benthamiana leaf agroinfiltration has gained great popularity among plant biotechnologists, and it is also the system of choice for plant-based bioproduction at industrial level 17 . Furthermore, the rich multi-omic resources made available recently completes the requirements for N. benthamiana to become a standard chassis for fast DBTL engineering 18,19 , without precluding the adaptation of FBP/eGFP to other experimental systems as tobacco/Arabidopsis protoplasts or seedlings 20 .…”
Section: Discussionmentioning
confidence: 99%
“…N. benthamiana leaf agroinfiltration has gained great popularity among plant biotechnologists, and it is also the system of choice for plant‐based bioproduction at industrial level (COVID vaccines grow on leaves, 2021). Furthermore, the rich multi‐omic resources made available recently completes the requirements for N. benthamiana to become a standard chassis for fast DBTL engineering (Kurotani et al ., 2023; Ranawaka et al ., 2022), without precluding the adaptation of FBP/eGFP to other experimental systems as tobacco/ Arabidopsis protoplasts or seedlings (Furuhata et al ., 2020).…”
Section: Discussionmentioning
confidence: 99%